Bioactive Compound Bisacurone in the Turmeric Extract (Turcuron) Prevents Non-alcoholic Fatty Liver Disease by Reduction of Lipogenesis - Gouthamchandra, Kuluvar; Sudeep, Heggar Venkataramana; Raj, Amritha; Ramanaih, Illuri; Siddappa, Chandrappa; Shyamprasad, Kodimule (Indian Journal of Pharmaceutical Education and Research, 2021)
Objectives: The current study was carried out to demonstrate potential role of Turcuron, a standardized turmeric extract containing 8% Bisacurone to protect against non-alcoholic fatty liver disease (NAFLD). Methods: HepG2 cell lines exposed to oleic acid (OA) and high-fat diet-induced hepatic steatosis in mice were used as experimental models to explore the hepatoprotective effects of Turcuron. The cytotoxicity was quantitatively assessed by MTT assay. Lipid accumulation and intracellular triglyceride level were evaluated by oil red O staining. Expressions of SREBP-1c and PPAR- γ proteins in the HepG2 cells and in HFD fed mice liver were examined by western blot. Results: Turcuron suppressed fatty acid synthesis and subsided the oleic acid-induced lipid accumulation in HepG2 cells. Moreover, Turcuron also decreased lipid accumulation in the liver of HFDfed mice compared with the control group. The expression of lipogenic genes involved in hepatic lipid metabolism SREBP-1cand PPAR-γ were decreased both in the HepG2 cells and in the liver of Turcuron supplemented mice. These results suggest that Turcuron may actively ameliorate non-alcoholic fatty liver disease. Conclusion: The findings of the present study provide corroborative scientific evidence that Turcuron may actively ameliorate non-alcoholic fatty liver disease.
Keywords: NAFLD; Bisacurone; SREBP-1; Oil- O red; HFD